ASSESSING CONNECTION QUALITY IN PASSENGER AIR TRANSPORT IN THE CONTEXT OF PRAGUE REGION DEVELOPMENT - Vladimír ĽUPTÁK; Ladislav BARTUŠKA; Paweł DROŹDZIEL (Scientific Journal of Silesian University of Technology. Series Transport)
The objective of this contribution is the application of a new methodology for assessing connectivity in passenger transport regarding selected tariff points accessibility in the context of developing the selected region. From the passenger´s point of view, it is necessary to specially assess the accessibility of lines within transportation, between the selected destinations using passenger air transport. The length of the travel time, the number of necessary transfers and the number of travel opportunities affects the possibilities of transport between place A and B. The connections and lines are thus influenced by many factors. This is the basic point to consider when designing a set of evaluation criteria for assessing the connectivity and in carrying out a case study for a specific region. In this paper, Václav Havel Airport in Prague (Czech Republic) with selected air transport connections were evaluated according to the proposed methodology.